2022
DOI: 10.1186/s12645-021-00110-x
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin-loaded folic acid-modified albumin nanoparticles (FA-BSANPs/BA) induce autophagy in MCF-7 cells via ROS-mediated p38 MAPK and Akt/mTOR pathway

Abstract: Background Breast cancer is the most frequently occurring cancer among women. Baicalin has been shown to inhibit breast cancer proliferation, but poor aqueous solubility and unknown mechanism of action limit its application. This study aimed to investigate the antiproliferative effects of baicalin-loaded folic acid-modified albumin nanoparticles (FA-BSANPs/BA) in breast cancer MCF-7 cells and its relationship with autophagy and ROS-mediated p38 MAPK and Akt/mTOR signaling pathways. Cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The effect of such signaling molecules is to increase the permeability of the mitochondrial membrane, thus making it easier for cytochrome c to be released from the mitochondria. In response to the apoptotic signal, caspase genes are activated, resulting in the cleavage of apoptosis‐related proteins (e. g. PARP), which is regulated by the Bcl proteins [38] . This study demonstrated that the synthesized nanoparticles inhibited the expression of Bcl‐2, increased the expression of BAX in a dose‐dependent manner, and that apoptosis can be induced by the change in expression of these genes.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The effect of such signaling molecules is to increase the permeability of the mitochondrial membrane, thus making it easier for cytochrome c to be released from the mitochondria. In response to the apoptotic signal, caspase genes are activated, resulting in the cleavage of apoptosis‐related proteins (e. g. PARP), which is regulated by the Bcl proteins [38] . This study demonstrated that the synthesized nanoparticles inhibited the expression of Bcl‐2, increased the expression of BAX in a dose‐dependent manner, and that apoptosis can be induced by the change in expression of these genes.…”
Section: Resultsmentioning
confidence: 74%
“…In response to the apoptotic signal, caspase genes are activated, resulting in the cleavage of apoptosis-related proteins (e. g. PARP), which is regulated by the Bcl proteins. [38] This study demonstrated that the synthesized nanoparticles inhibited the expression of Bcl-2, increased the expression of BAX in a dose-dependent manner, and that apoptosis can be induced by the change in expression of these genes. Activating all phases of the cancer immunity process, pro-inflammatory cytokines (for instance, TNF-α) can contribute to cancer therapy.…”
Section: Discussionmentioning
confidence: 72%
“…By stopping the cell cycle, the P53 protein prevents cancer cells from proliferating 53 . After apoptosis signals are received, caspase 3, -6, -7, -8, and -9 are activated, cleaving apoptosis-related proteins 54 . Apoptosis and the production of cytokines are both regulated by caspase-8, a cysteine protease.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, baicalin was loaded with folic acid-modified albumin nanoparticles (FA-BSANPs/BA) to improve its biocompatibility and prolong its circulation time in vivo. The FA-BSANPs/BA nanoparticles were found to elevate ROS levels, inactivate AKT/mTOR signaling, and induce cytotoxic autophagy and apoptosis in breast cancer [ 137 ]. These results demonstrate that baicalin can regulate ROS-mediated autophagy in cancer.…”
Section: Phytochemicals Targeting Ros and Autophagy For Cancer Therapymentioning
confidence: 99%